How to Improve Students' Creative Thinking Skills In Learning Prism Nets Through Problem-Based Learning? - Susanto, Hessy Susanti Hobri (International Journal of Scientific Research and Management (IJSRM), 2016)
Creative thinking is one's ability to find several alternative answers. In this research, by using qualitative research methods, students' creative thinking is developed through learning with Problem-based Learning model on the perimeter material of prism nets. The purpose of this study is to improve student creativity. Creative thinking of students is analyzed against student learning outcomes based on predetermined guidelines. In addition, through the implementation of learning this study aims to reduce the formula of the number of perpendicular triangular prism nets with upright sides clustering and circumference; The number of perpendicular rectangular prism nets with upright sides clustering and circumference; and the number of the perpendicular pentagon prism nets with upright sides clumping and perimeter which are then formulated in general by the researcher. The result of this research is the formulation of the number of the perpendicular regular n-facet prism nets with the upright side clumped ie n2 , and the circumferential formula of the perpendicular regular n-facet prism nets with the upright side clumped ie Kjn = 2 ((2n - 2)a + t) , n ≥ 3.